2x+1 - x-4 = -10x+13
x-3 x+5 x+5
= (x-3)(x+5) (2x+1 - x-4) = (x-3)(x+5) (-10x+13)
(x-3 x+5) ( x+5 )
= (2x+1)(x+5)-(x-4)(x-3)=(x-3)(-10x+13)
= 2x²+10x+1x+5-x²+3x-4x+12=-10x²+13x+30x-39
= 2x²+11x+5-x²-1x+12=-10x²+43x-39
= 2x²-x²+10x²+11x-1x-43x+5+12+39=0
= 11x²-33x+56=0
= ?????
any help will be utmostly appreciated
x-3 x+5 x+5
= (x-3)(x+5) (2x+1 - x-4) = (x-3)(x+5) (-10x+13)
(x-3 x+5) ( x+5 )
= (2x+1)(x+5)-(x-4)(x-3)=(x-3)(-10x+13)
= 2x²+10x+1x+5-x²+3x-4x+12=-10x²+13x+30x-39
= 2x²+11x+5-x²-1x+12=-10x²+43x-39
= 2x²-x²+10x²+11x-1x-43x+5+12+39=0
= 11x²-33x+56=0
= ?????
any help will be utmostly appreciated